Gejala Perubahan Penguasaan Kebun Plasma dan Berkembangnya Ketidakmerataan Pendapatan pada Komunitas Petani PIR-BUN - Undang Fadjar; Bambang Dradjat; Melani A. Sunito (Jurnal Agro Ekonomi, 2002)
EnglishOne of the programs for the village development that fulfill the goal for the growth and equality distribution of income is the partnership program for the Perusahaan Inti Rakyat Perkebunan (PIR-BUN). The objective of this program, beside to increase the productivity and the efficiency of public plantation effort is also to grant the opportunity for managing a business for the poverty stratum that do not possess plantation and fund but have the human resources capability. Then, all participants of the program are given a plasma plantation with the same width. Therefore, in support of the PIR-BUN program, the plasma plantation is the bridging for a farmer to attain the chance to increase their financial income. This research is done as a study case toward the four locations of PURBUN rubber plants that was chosen by purposive sampling. The four locations are consist of Rimbo Bujang (RB), Jambi, (Talang Jaya) Sumatera Selatan, Monterado-Kinande (MD) Kalimantan Barat, and Danau Salak (DS), Kalimantan Selatan. Data and the information was gathered and analyzed using quantitative analysis (t-test), Gini index, and descriptive statistic). The result of this research shows that in all locations there has been a change of authorized foundation of the plasma plantation, which causes not only the permanent ownership of the foundation but also the temporary ownership of the foundation. Beside that, the changes of the ownership, the width of the foundation, and the changes of the position of the ownership from being the "owner of the foundation" becoming the "owner of the non-foundation" has made a community of the PIR-BUN farmers posses the social layers more than one. Along with that, the result of t-test of the two average values of the income between the layers of the income of the PIR-BUN shows that the average of income between each layers of PIR-BUN farmers are different. The analysis of the "Gini Index" and the analysis of the "Society group income based on the World Bank concept" shows that on the PIR-BUN community in all research location there has been an inequality in the category of "medium" or low.IndonesianSalah satu program pembangunan pedesaan yang berupaya memenuhi tujuan pertumbuhan dan pemerataan diantaranya adalah program kemitraan Perusahaan Inti Rakyat Perkebunan (PIR-BUN). Sasaran program ini, selain untuk meningkatkan produktivitas dan efisiensi usaha perkebunan rakyat juga untuk memberikan peluang usaha seluas-luasnya bagi lapisan masyarakat miskin yang tidak memiliki kebun dan modal tetapi memiliki sumberdaya tenaga kerja. Berkaitan dengan itu, penelitian ini dilakukan untuk menjawab apakah setelah 10 tahun lebih terjadi perubahan penguasaan kebun plasma serta ketidakmerataan pendapatan pada petani. Penelitian ini dilaksanakan pada empat lokasi PIR-BUN tanaman karet yang dipilih secara purposif, yaitu Rimbo Bujang (RB) Jambi, Talang Jaya (TJ) Sumatera Selatan, Monterado-Kinande (MD) Kalimantan Barat, dan Danau Salak (DS) Kalimantan Selatan. Analisis data dilakukan secara kuantitatif (uji beda nyata/uji-t, indeks gini, dan statistik deskriptif) dan analisis kualitatif. Hasil penelitian menunjukkan bahwa di seluruh lokasi penelitian telah terjadi perubahan kelembagaan penguasaan kebun plasma, sehingga selain terdapat kelembagaan pemilikan tetap terdapat pula kelembagaan pemilikan sementara terutama melalui kelembagaan bagi hasil. Selain itu, perubahan-perubahan luas pemilikan, luas penggarapan, dan perubahan posisi pemilik tetap dari "pemilik penggarap" menjadi "pemilik bukan penggarap" telah membuat komunitas petani PIR-BUN memiliki lapisan sosial lebih dari satu. Bersamaan dengan itu, hasil uji beda dua nilai rataan pada taraf nyata 20 persen terhadap pendapatan komunitas petani PIR-BUN menunjukkan bahwa rata-rata pendapatan antar lapisan petani PIR-BUN berbeda. Demikian halnya, analisis "lndeks Gini" dan analisis "pendapatan kelompok masyarakat berdasarkan konsep Bank Dunia", bahwa pada komunitas petani PIR-BUN di semua lokasi penelitian telah terjadi ketidakmerataan dengan kategori "sedang" atau rendah.